Hubungan Kekuatan Otot Tungkai Dengan Keseimbangan Dinamis Dan Kelincahan Pada Pemain Bulu Tangkis Rekreasional Di Kota Denpasar - I Wayan Denny Darmawan; Sayu Aryantari Putri Thanaya; Ni Wayan Tianing; Indah Pramita (Universitas Pahlawan Tuanku Tambusai, 2026)
Badminton is a sport that requires physical abilities such as lower limb muscle strength, dynamic balance, and agility to support movement performance on the court. These components play important roles in body stability, changes of direction, acceleration, deceleration, and movement speed. This study aimed to determine the relationship between lower limb muscle strength, dynamic balance, and agility among recreational badminton players in Denpasar City. This study used an observational analytic design with a cross-sectional approach. A total of 60 recreational badminton players were selected using purposive sampling. Lower limb muscle strength was measured using a leg dynamometer, dynamic balance was assessed using the Y-Balance Test, and agility was evaluated using the Agility T-Test. Data were analyzed using Spearman rho correlation because one variable was not normally distributed. The results showed no significant relationship between lower limb muscle strength and dynamic balance (r = 0.215; p = 0.100). However, a significant relationship was found between lower limb muscle strength and agility (r = -0.618; p = 0.000). The negative correlation indicates that higher lower limb muscle strength is associated with shorter Agility T-Test completion time, reflecting better agility performance. In conclusion, lower limb muscle strength was not significantly associated with dynamic balance but was significantly associated with agility among recreational badminton players in Denpasar City.